IMPLEMENTASI ALGORITMA KNUTH MORRIS PRATT PADA APLIKASI SINOPSIS FILM BIOSKOP BERBASIS WEB - Nia Novianti; Ricky Crist G Imanta Kembaren; Dessy Milbina Br Bangun; Nasib Marbun (STMIK Budi Darma, 2019)
Synopsis of cinema films is a description that illustrates the storyline of a film that will be screened on a bisocope with a brief study but can convey information related to the outline of a cinema film story that will be played on a bisocope. The number of synopsis of cinema films that are stored in the database of a system affects the use of time and space needed in the process of searching synopsis data. Synopsis search for cinema films can not be separated from the existence of string matching to match keywords searched with cinema film data stored in the database system, the better the way the string matching algorithm is applied to the search feature in a system, the easier it is for users to find data synopsis of cinema films sought. Knuth Morris Pratt uses the stage of shifting text patterns from left to right in the process of matching strings in text if there is a mismatch between the character pattern and the text character. In this study the Knuth Morris Pratt algorithm is used to make it easier for users to find synopsis data of cinema films that are searched according to the keyword searches performed on the search feature in the system.Keywords: synopsis, movie theaters, String Matching, Knuth Morris Pratt